Pengaruh Jintan Hitam (Nigella Sativa) pada Konversi Sputum dan IFN-γ Penderita Tuberkulosis Paru yang Mendapat OAT Kategori I pada Akhir Minggu Kedua Fase Intensif: [The Role of Nigella sativa in Sputum Conversion and the Increase of Interferon-γ in Pulmonary Tuberculosis Patient] - Ahmad Nurdin; Helmia Hasan (Faculty of Medicine Universitas Airlangga, 2015)
Background: Primary resistance is the resistance that occurs in patients who have never received treatment OAT or had ever received treatment OAT is less than 1 month. The incidence of primary MDR in Central Java in 2006 2.07%. Extrapulmonary TB about 15-20% of all cases of TB, and TB lymphadenitis is the highest form (35% of all extrapulmonary TB). Patients with decreased immune systems (SLE) can increase the incidence of TB. Research in Spain get 6x higher TB incidence in patients with SLE. Case: We present the case of 19 year old woman SLE who received treatment for 11 months whose came with shortness of breath and chronic cough since 2 month prior to admission. In physical examination we found right and left submandibula lymphonodi enlargement as solid, slightly mobile nodule with diameter 3 cm. Chest X ray showed lung inflammation which suspicion of specific process and minimal left pleural effusion, and concluded as pulmonary TB. FNAB confirmed lymphadenitis TB with granulomatous inflammation. One of AFB result is positive and Gene Xpert is M.tb positive with rifampicin resistant that make this patient categorized as primary MDR TB with lymphadenitis TB. This patient received Pirazinamid 1500 mg, Ethambutol 800 mg, Kanamicin 750 mg, Levofloxacin 750 mg, Ethionamide 500 mg, Cicloserin 500 mg, and B6 100 mg. Conclusion: MDR TB in general occur in patients with a history of OAT previous TB (MDR TB secondary). Primary MDR TB with lymphadenitis tb is a rare case, but can occur on the condition that decreases the immune system, one of SLE. This involves multiple immune disorders caused by the use of long-term immunosuppressive therapy.